The Effect of Water Intake during Pregnancy on Birth Weight: Pengaruh Asupan Air selama Kehamilan pada Berat Lahir Bayi - Tria Rosemiarti; Hardinsyah Hardinsyah; Sudung O. Pardede; Parlindungan Siregar; Budi I. Santoso; Netta M. Putri; Ratu S. Hanifah (Indonesian Socety of Obstetrics and Gynecology, 2023)
AbstractObjective: This systematic review aimed to investigate theeffect of water intake during pregnancy on infant birthweight.Methods: A comprehensive search was conducted usingthe keywords